Institution repository of National Aviation University – new online resource of electronic library - Іванкевич, О. В.; Вахнован, В. Ю. (Proceedings of National Aviation University (archive), 2013)
The principles of institutional repository of the National Aviation University based on Dspace software environment are considered. Here are considered the principles of forming the repository content, which must consist of materials of scientific conferences, funds of faculties and departments, annotated reports, research topics, articles of scientific journals, student theses and dissertations abstracts, patents, publications, independent researchers and others